Intramolecular Cyclization of N-Propargylic Amides without Transition-Metal Catalysis for Synthesis of Fluoroalkylated Oxazoles: Using Carboxylic Acid Anhydrides as the Fluoroalkyl Source - Sugiishi, Tsuyuka; Motegi, Ryohei; Amii, Hideki (Synthesis, 2023)
Synthesis of 2-fluoroalkylated oxazoles was developed by transition-metal-free intramolecular cyclization of N-propargylic amides, which are prepared from propargylic amines by employing a small excess of commercially available fluorocarboxylic acid anhydrides as fluoroalkyl sources, under basic conditions. Oxazoles bearing a trifluoromethyl, pentafluoroethyl, or heptafluoropropyl group at the C2 position and functional groups on the C4 and/or C5 positions are obtained in moderate to high yields by controlling the reaction conditions.
Keywords: fluoroalkyl substituents; carboxylic acid anhydrides; N-propargylic amides; oxazoles; cyclization